Plasmatron for ion-plasma surface of glass treatment at atmospheric pressure - Шрам, Александр Анатольевич (Technology audit and production reserves, 2015)
Main mass of glass processing research is devoted to vacuum methods and to creation of non-penetrating coatings that are subject to physical and chemical impact. Therefore, the development of plasma devices that improve the efficiency of processing through the organization process at atmospheric pressure is an actual problem. The article suggests construction and studies operation modes of DC-arc plasmatron, which eliminates the need for powder coating material of a specific particle size, allows using as source material of introduction aqueous solutions of salts and increases the effective utilization of the implementation material at surface treatment of the glass. In view of the construction features of the developed plasmatron and its working conditions, as well as the weak dependence of the voltage of the electric arc on the Knudsen criterion (complex pd) a simplified equation of the current-voltage characteristics is proposed. The calculation of the current-voltage characteristics of the proposed dependence is in satisfactory agreement with the experimental data. The coefficient of efficiency of the developed plasmatron is 63 ... 80 %.